PENGARUH PENERAPAN SKS, MOTIVASI EKSTRINSIK, DAN DISIPLIN BELAJAR TERHADAP PRESTASI BELAJAR EKONOMI SISWA KELAS XI IPS SMAN 3 PURWOKERTO - Ikke Iryanti; Ratno Purnomo (Fakultas Ekonomi dan Bisnis, Universitas Jenderal Soedirman, 2019)
Abstract The purpose of the study was to analyze the effect of applying credits, extrinsic motivation, and learning discipline on economic learning achievement in class XI IPS SMAN 3 Purwokerto. This research uses a quantitative approach with a survey method. The population of this research was all students of class XI of SMAN 3 Purwokerto. To analyze hypotheses using multiple linear regression analysis. The Conclusions are: 1. The application of the Semester Credit System (SKS) does not influence the economic Significantly learning achievement of students of class XI IPS SMAN 3 Purwokerto; 2. extrinsic motivation has a positive effect on students' achievement of economic learning in class XI IPS SMAN 3 Purwokerto; 3. Learning discipline has a positive economic effect on the learning achievement of students of class XI IPS SMAN 3 Purwokerto; 4. Keywords: SKS application, extrinsic motivation, learning discipline, Learning Achievement.